We Are Star Stuff: Transgender Cinema and Disney's Wishing Star. - Hester, Jennessa (Marvels & Tales, 2026)
The article focuses on how Disney's wishing-star motif functions as a queer and transgender cinematic symbol, using films such as Pinocchio, The Princess and the Frog, and Wish to explore themes of embodiment, transformation, and identity. Topics include transgender representation and change, the cultural and narrative significance of the Disney wishing star, and the relationship between celestial imagery, selfhood, and queer experiences.